Hašek's Fiction in Texts, Theater, and Film (František A. Podhajský (ed.), Fikce Jaroslava Haška) - Mareš, Petr (Iluminace, 2017)
Review of František A. Podhajský (ed.), Fikce Jaroslava Hašek
Keywords: book reviews; film literature